Enhanced conversion of CO2 into O2-free fuel gas via the Boudouard reaction with biochar in an atmospheric plasmatron. Issue 45 (March 2021) - Huang, Jingying; Zhang, Hao; Tan, Qinhuai; Li, Li; Xu, Ruiyang; Xu, Zemin; Li, Xiaodong
Highlights: Energy efficiency can reach 36.4 % in the plasmatron CO2 decomposition process. Max. CO2 conversion is largely enhanced from 6.9%–21.3% with biochar addition. Boudouard reaction contributes >96.0 % of CO2 conversion in the presence of biochar. O2-free fuel gas with high CO content can be produced in the presence of biochar. Abstract: In this work, CO2 reaction with biochar via the Boudouard reaction (CO2 + C → 2CO) has been investigated in an atmospheric non-thermal plasmatron for the first time, aiming for enhanced conversion of CO2 into O2 -free fuel gas (mainly CO). The motion behavior and electrical characteristics of the plasmatron in CO2 was studied to understand its physical characteristics. Both the CO2 decomposition reaction and CO2 reaction with biochar were evaluated in the plasmatron under different flow rates and applied voltages. The results showed that the discharge experiences a consecutive circle of breakdown – elongation – extinguishment - re-breakdown outside of the electrode region. For the CO2 decomposition process without biochar, a high voltage of 10 kV shifts the optimal flow rate to a remarkably higher value, yielding a CO2 conversion of 6.9 % and an energy efficiency of up to 36.4 % at flow rate = 13 L/min. In the presence of coconut shell biochar, the net Boudouard reaction becomes the dominant contributor to CO2 conversion with contributions of up to >96.0 % (applied voltage =10 kV). As a result, a significantly enhanced CO2 conversion of up to 21.3 % can be achieved in comparison to the CO2 decomposition process, simultaneously with a dramatically higher CO (e.g., increases from 2.31% to 34.08%) but remarkably lower O2 concentration (e.g., decreases from 1.0 % to 0.06 %) in the products. The immediate study reveals that the plasmatron assisted CO2 reaction with biochar via the Boudouard reaction is a promising route for energy efficient CO2 conversion into O2 -free fuel gas.